PENENTUAN WAKTU STANDAR GUNA MEMAKSIMALKAN KAPASITAS PRODUKSI PRODUK MEDIA TANAM - Moh. Gunawan Pane; Handy Febri Satoto (LPPM Universitas Bina Bangsa, 2023)
CV. Wira Jaya Nusantara is an agricultural product company. This company has employees in charge of producing planting media soil products. Planting media production employees at CV. Wira Jaya Nusantara has 10 employees with a total production of 135 planting media products per day. The planting media production workforce only has 4 workers, with a fairly large number of daily targets, workers experience quite a large workload due to quite a lot of production work on a scale. It is hoped that this research is the optimization of production based on working time. Data collection was carried out by means of the stopwatch time study method. The calculation results will be the beginning of determining the standard time of the planting media production process. Based on the analysis of working time, the standard time obtained by workers in the methane growing media production section is 29.47 minutes for mixing ingredients, 19.58 minutes for filling materials, 12.11 minutes for product sealers and product stickers is 5.58 minutes. While the npk planting media is 43.80 minutes for filling materials, 32.86 minutes for product sealers and product stickers is 15.12 minutes. Based on these calculations, production demand can be achieved with methane product conditions, mixing ingredients 2 regular time workers and 2 over time workers, filling materials 2 regular time workers and 1 over time worker, product sealer 1 regular time worker and 1 over time worker, and product stickers for 1 regular time worker. for NPK products, 1 regular time worker fills materials, 1 regular time worker product sealer and 1 regular time worker for product stickers